83P Analysis of predictive factors in non-small cell lung cancer patients treated with nivolumab. (15th December 2019) - Azuma, K; Tamiya, A; Adachi, Y; Enomoto, T; Kouno, S; Taniguchi, Y; Saijo, N; Okishio, K; Atagi, S
Abstract: Background: Immune checkpoint inhibitors (ICI) have been established as a novel strategy for non-small cell lung cancer (NSCLC). However, definitive biomarkers that can predict response to ICI therapy remains established. Some prostate factors are suggested, Neutrophile-lymphocyte ratio (NLR), advanced lung cancer inflammation index (ALI), Lung Immune Prognostic Index (LIPI), then we investigate their efficiency. Methods: The medical records of consecutive 296 patients with NSCLC who were treated with nivolumab at Kinki-chuo Chest Medical Center between December 17, 2015 and December 31, 2018 were collected. Nivolumab was the only ICI validated for advanced NSCLC in a second-line treatment setting. We investigated the relationship between median progression free survival (PFS) and already known prognostic factors (NLR, ALI, LIPI and so on). Results: The median age was 70 (range, 40-90) years. 206 patients were male, and 224 patients were good PS group (PS 0-1). The median PFS was 3.0 months in all patients. The median PFS was 4.7 (NLR<4) versus 2.9months (NLR ≦4) [hazard ratio (HR) =0.43; 95% confidence interval (CI) =0.26-0.93], 4.0 (ALI≧18) versus 1.4 months (ALI <18) [HR = 0.56; 95%CI =0.44-0.73], 3.2 (LIPI 0-1) versus 1.3 months [HR = 0.66; 95%CI =0.48-0.89]. Conclusion: NLR, ALI and LIPI score have the potential to be predictive factors of ICI response in NSCLC patients. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: A. Tamiya: Research grant / Funding (self): Taiho; Research grant / Funding (self): pfizer; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Ono pharmaceutical; Research grant / Funding (self): Bristol-Myers Squibb; Research grant / Funding (self): Chugai pharmaceutical; Research grant / Funding (self): Eli Lilly; Research grant / Funding (self): Boehringer Ingelheim; Research grant / Funding (self): MSD; Research grant / Funding (self): Kissei. S. Atagi: Research grant / Funding (self): Ono pharamaceutical; Research grant / Funding (self): Bristol-Myers Squibb; Research grant / Funding (self): Pfizer; Research grant / Funding (self): Taiho; Research grant / Funding (self): Chugai pharmaceutical; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Eli Lilly; Research grant / Funding (self): Boehringer Ingelheim; Research grant / Funding (self): Yakult pharmaceutical; Research grant / Funding (self): MSD. All other authors have declared no conflicts of interest.